Keratoacanthoma of the Head and Neck: A Mini Review - Abdelrahim, Laila; Najat Ghuela, (AlQalam Journal of Medical and Applied Sciences, 2025)
Keratoacanthoma (KA) is a keratinocyte-derived, rapidly growing skin neoplasm. A well-differentiated lesion often exhibits spontaneous regression. KA typically presents as a dome-shaped lesion with a central keratin plug, demonstrating a symmetrical, well-circumscribed architecture histologically. This review discusses the epidemiology, clinical presentation, histopathology, differential diagnosis, and management of KA with emphasis on lesions occurring in the head and neck region.